A SOCIAL MEDIA SENTIMENT ANALYSIS ON RENEWABLE ENERGY FORMS - Şenyapar, Hafize Nurgül Durmuş (Fırat University, 2024)
This study conducts a sentiment analysis of public opinions on various energy sources, including hydro, solar, wind, and nuclear, using data from social media platforms like Facebook, Instagram, Quora, and Reddit. A dataset of 3,269 mentions and examining interactions, shares, and likes offers an extensive view of the current discourse on these energy forms. The methodology combines quantitative sentiment analysis with qualitative content examination to uncover underlying themes. The findings reveal strong positive sentiment towards renewable energy, mainly hydro and solar power, often described as “clean,” “sustainable,” and “efficient.” Hydro energy is highly regarded due to its minimal environmental impact, while solar energy is praised for combating climate change and technological advancements. Wind energy faces criticism for visual and noise pollution concerns and potential effects on wildlife, while nuclear power generates negative sentiments primarily due to safety and waste management issues. These results have important implications for shaping effective marketing strategies within the renewable energy industry.

Bu çalışma, Facebook, Instagram, Quora ve Reddit gibi sosyal medya platformlarından elde edilen verilerle hidro, güneş, rüzgâr ve nükleer gibi çeşitli enerji kaynakları hakkındaki halk görüşlerinin duygu analizini gerçekleştirmektedir. 3,269 bahsetme verisi ile etkileşimler, paylaşımlar ve beğeniler incelenerek bu enerji formlarıyla ilgili güncel tartışmalara kapsamlı bir bakış sunulmaktadır. Yöntem, duygu analizini nicel verilere dayandırarak altta yatan temaları ortaya çıkarmak için nitel içerik incelemesiyle birleştirilmektedir. Sonuçlar genellikle “temiz,” “sürdürülebilir” ve “verimli” olarak tanımlanan yenilenebilir enerjiye, özellikle hidro ve güneş enerjisine karşı güçlü bir olumlu duygu ortaya koymaktadır. Hidro enerjisi, çevresel etkisinin minimum olduğu algısı nedeniyle yüksek bir itibara sahiptir; güneş enerjisi ise iklim değişikliği ile mücadele ve teknolojik ilerlemeler için övgü almaktadır. Rüzgâr enerjisi, görsel ve ses kirliliği endişeleri ve potansiyel vahşi yaşam etkileri nedeniyle eleştirilirken nükleer enerji güvenlik ve atık yönetimi sorunları nedeniyle olumsuz duygular uyandırmaktadır. Bu sonuçlar, yenilenebilir enerji endüstrisi içinde etkili pazarlama stratejileri oluşturmak için önemli sonuçlar sunmaktadır.
Yenilenebilir Enerji Türleri Üzerine Bir Sosyal Medya Duygu Analizi
Keywords: Digital Advertising; Dijital Reklamcılık; Advertising Studies; Reklam Araştırmaları; Advertising Strategies; Reklam Stratejileri; Advertising Media Planning; Reklam-Medya Planlamaları